Degree of root canal transportation of three rotary instrumentation systems: a cone-beam computed tomography study - Guzmán, Carmen Lucía; Salazar, Daniela; González, Fermín E.; Alcota, Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Introduction: the preparation of root canals should provide a progressively tapered shape from apical towards coronal, without producing procedural errors. Transportation is defined as the change in location of the root canal with respect to its original position, producing unbalanced wear in any of the dentine walls in relation to their original anatomy. New rotary endodontic instruments have been developed during the latest decade with nickel-titanium (NiTi), a material that provides increased flexibility and fracture strength, reduces working time and operator fatigue, and facilitates proper canal preparation while reducing procedural errors. Method: this was an in vitro study on 45 upper and lower human root canals with moderate to severe curvatures, selected through conventional radiographs. They were sorted out in 3 groups of 15 canals that were prepared with the aforementioned rotary instrumentation systems. The cone beam technology was used to record images before and after instrumentation; these images were obtained by means of a silicon rim that formed a dental arch intended to serve as a post instrumentation reproducible assembly. Measurements were made in sections taken at 2, 4, 6, and 8 mm from the apex via instrumented canal; four measurements were made in each section: the buccal, lingual, furcation and free side walls. The obtained data were analyzed with the Wilcoxon test for paired samples and the ANOVA test. Results and conclusions: the results suggest that the ProTaper Universal system (Dentsply-Maillefer, Switzerland) produces the most root canal transportation at the middle third compared with the RaCe (FKG-Dentaire, Switzerland) and K3 (SybronEndo, USA) systems. Also, the K3 system showed more conservative wear at 2, 4 and 6 mm of root canal instrumentation, which makes it suitable for instrumenting thin and curved canals. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">